2008
DOI: 10.4085/1062-6050-43.2.190
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Value of the Clarke Sign in Assessing Chondromalacia Patella

Abstract: Context: Various techniques have been described for assessing conditions that cause pain at the patellofemoral (PF) joint. The Clarke sign is one such test, but the diagnostic value of this test in assessing chondromalacia patella is unknown.Objective: To (1) investigate the diagnostic value of the Clarke sign in assessing the presence of chondromalacia patella using arthroscopic examination of the PF joint as the ''gold standard,'' and (2) provide a historical perspective of the Clarke sign as a clinical diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 30 publications
0
32
0
1
Order By: Relevance
“…Although the patellofemoral grind test has been suggested as a method for detecting chondromalacia patella or patellofemoral pain syndrome, the test is poorly validated for this, and its significance has been questioned . A recent study showed that the typical clinical examination measures (patellofemoral crepitus and pain with patellofemoral compression) that were commonly thought to represent underlying patellofemoral joint pathology did not discriminate knees with patellofemoral OA from knees with tibiofemoral OA or without OA .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the patellofemoral grind test has been suggested as a method for detecting chondromalacia patella or patellofemoral pain syndrome, the test is poorly validated for this, and its significance has been questioned . A recent study showed that the typical clinical examination measures (patellofemoral crepitus and pain with patellofemoral compression) that were commonly thought to represent underlying patellofemoral joint pathology did not discriminate knees with patellofemoral OA from knees with tibiofemoral OA or without OA .…”
Section: Discussionmentioning
confidence: 99%
“…The patellofemoral grind test is a simple clinical test used in practice for the evaluation of anterior knee pain. In this setting, a positive test may suggest the presence of chondromalacia patella or patellofemoral pain syndrome . Such a positive test, however, is a purely theoretical construct.…”
Section: Introductionmentioning
confidence: 99%
“…16 Additionally, the presence of pain with palpation of the apex and medial facet of the patella (yes or no) was assessed, and Clarke's compression test was performed (positive or negative). 6 Strength of the quadriceps and hip musculature for abduction and external rotation was measured using a handheld dynamometer (MicroFET2; Fabrication Enterprises Inc, Elmsford, NY), which is a reliable method to measure strength in individuals with PFP. 18 Strength measurements were repeated 3 times, and the mean of the highest 2 values was used for analyses (Newton meters per square centimeter).…”
Section: Measurementsmentioning
confidence: 99%
“…The presence of pain indicated a positive diagnosis. 19 Participants with a history of neuromuscular or musculoskeletal disorders; any balance, vestibular, or visual problems; or a significant injury to either lower extremity aside from unilateral PFPS were excluded from the study. The study was approved by the ethics committee of the University of Social Welfare and Rehabilitation Sciences, and all participants provided written informed consent.…”
Section: Participantsmentioning
confidence: 99%